1988
DOI: 10.1113/jphysiol.1988.sp017056
|View full text |Cite
|
Sign up to set email alerts
|

Development of sodium and chloride transport across fetal and newborn rat stomach in vitro.

Abstract: 3. However, on fetal day 20, neutral absorption of NaCl was no longer observed but amiloride had inhibited electrogenic absorption of Na+, and significant active secretion of Cl-was observed (J" = -1-3 + 0-6 pequiv cm-2 h-1). On day 21 (i.e. 24 h before birth), values for JNa )Jclt, and Is were not different from those determined on adult gastric mucosa.4. After birth, NaCl transport continued to exhibit its prenatal characteristics on day 5 but not on day 12, when Na+ and Cl-were both absorbed; on that day, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The gallbladder was opened, rinsed with Ringer solution and vertically mounted as flat sheets in Ussingtype chambers [8] (exposed surface area=0.14 or 0.22 cm 2). A circle of high-viscosity silicone gel (Bayer) was applied to the inner rim of the interface between the two chamber halves to minimize edge damage.…”
Section: Study Of Na+ Fluxesmentioning
confidence: 99%
“…The gallbladder was opened, rinsed with Ringer solution and vertically mounted as flat sheets in Ussingtype chambers [8] (exposed surface area=0.14 or 0.22 cm 2). A circle of high-viscosity silicone gel (Bayer) was applied to the inner rim of the interface between the two chamber halves to minimize edge damage.…”
Section: Study Of Na+ Fluxesmentioning
confidence: 99%
“…Tissue conductance and permeability measurements Pieces of colon (0.5 cm 2 ) were mounted in Ussing chambers as previously described (Ducroc et al, 1988). Electrogenic ion transport was monitored as short-circuit current (Isc) using an …”
Section: Image Acquisition and Analysesmentioning
confidence: 99%
“…We previously demonstrated that in the rat, the development of H '" and CI -secretion was characterized by a fetal phase of emergence and maturation, followed by a postnatal phase of reduced secretion (1-4). By day 12 of life, the basal secretion of H + and CI-ions, as with the activity of gastric H + , K + -ATPase, dropped to zero (4)(5)(6), and the parietal cell was still insensitive to exogenous histamine (5). Since thi s gradual inhibition of acid secretion and reduced responsiveness to histamine were observed after 5 days of suckling (5,6), we postulated that a short-term milk diet might interfere with the histaminergic regulation of acid secretion.…”
Section: Inhibition By Cow's Milk Of Histamine-induced Gastric Acid S...mentioning
confidence: 99%